Identification of Novel Bioactive Compound Derived from Rheum officinalis against Campylobacter jejuni NCTC11168 - Mohammed Yosri; Basma H. Amin; Nermine N. Abed; Amal S. Elithy; Sayed M. Kareem; Nagwa M. Sidkey (The Scientific World Journal, 2020)
Gastric diseases are increasing with the infection of Campylobacter jejuni. Late stages of infection lead to peptic ulcer and gastric carcinoma. C. jejuni infects people within different stages of their life, especially childhood, causing severe diarrhea; it infects around two-thirds of the world population. Due to bacterial resistance against standard antibiotic, a new strategy is needed to impede Campylobacter infections. Plants provide highly varied structures with antimicrobial use which are unlikely to be synthesized in laboratories. A special feature of higher plants is their ability to produce a great number of organic chemicals of high structural diversity, the so-called secondary metabolites. Twenty plants were screened to detect their antibacterial activities. Screening results showed that Rheum officinalis was the most efficient against C. jejuni. Fractionation pattern was obtained by column chromatography, while the purity test was done by thin-layer chromatography (TLC). The chemical composition of bioactive compound was characterized using GC-MS, nuclear magnetic resonance, and infrared analysis. Minimal inhibitory concentration (MIC) of the purified compound was 31.25 µg/ml. Cytotoxicity assay on Vero cells was evaluated to be 497 µg/ml. Furthermore, the purified bioactive compound activated human lymphocytes in vitro. The data presented here show that Rheum officinalis could potentially be used in modern applications aimed at the treatment or prevention of foodborne diseases.